Investigations on the structural, optical and electronic properties of Nd doped ZnO thin films - Subramanian, M.; Thakur, P.; Gautam, S.; Chae, K. H.; Tanemura, M.; Hihara, T.; Vijayalakshmi, S.; Soga, T.; Kim, S. S.; Asokan, K.; Jayavel, R. (IOP PUBLISHING LTD, 2009)
We report the synthesis and characterization of Nd doped ZnO thin films grown on Si (100) substrates by the spray pyrolysis method. The surface morphology of these thin films was investigated by scanning electron microscopy and shows the presence of randomly distributed structures of nanorods. Grazing angle x-ray diffraction studies confirm that the doped Nd ions occupied Zn sites and these samples exhibited a wurtzite hexagonal-like crystal structure similar to that of the parent compound, ZnO. The micro-photoluminescence measurement shows a decrease in the near band edge position with Nd doping in the ZnO matrix due to the impurity levels. The near-edge x-ray absorption fine structure (NEXAFS) measurements at the O K edge clearly exhibit a pre-edge spectral feature which evolves with Nd doping, suggesting incorporation of more charge carriers in the ZnO system and the presence of strong hybridization between O 2p-Nd5 d orbitals. The Nd M-5 edge NEXAFS spectra reveal that the Nd ions are in the trivalent state.
Keywords: RAY-ABSORPTION SPECTROSCOPY; VISIBLE-LIGHT IRRADIATION; NANOWIRE ARRAYS; SPRAY-PYROLYSIS; PHOTOLUMINESCENCE; NANOSTRUCTURES; FABRICATION; GREEN; GD